2004
DOI: 10.1055/s-2004-837280
|View full text |Cite
|
Sign up to set email alerts
|

Trinken - aber was? - Heilwässer in der Harnsteinmetaphylaxe

Abstract: Das Harnsteinleiden ist mit einer Prä-valenz von 4-5 % eine häufige Erkrankung in Mitteleuropa. Eine aktuelle epidemiologische Studie aus dem Jahr 2001 ergab für die Bundesrepublik Deutschland zwischen 1979 und 2000 einen Anstieg von 4,0 auf 4,7 %. Insbesondere bei den Älteren ist die Prä-valenz seit 1979 stärker angestiegen, wobei Männer immer noch stärker betroffen sind als Frauen. Die Inzidenz lag im Jahr 2000 bei 1,5 %, während sie 1979 noch 0,5 % betrug. Daraus ergibt sich, dass in Deutschland pro Jahr et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Health. Urine pH of healthy subjects ranges usually between 5.8 and 6.8, depending on the consumed diet [49]. It has been shown that vegans have a higher urine pH (6.7) than omnivores (6.2) [50].…”
Section: Implications For Humanmentioning
confidence: 99%
See 2 more Smart Citations
“…Health. Urine pH of healthy subjects ranges usually between 5.8 and 6.8, depending on the consumed diet [49]. It has been shown that vegans have a higher urine pH (6.7) than omnivores (6.2) [50].…”
Section: Implications For Humanmentioning
confidence: 99%
“…Terefore, the most obvious impact on human health relates to the modulation of kidney stone risk (calcium oxalate stones, uric acid stones) due to changes in urinary pH. While a low urine pH favors crystallization, an elevated urine pH counteracts crystallization [49,53]. Moreover, bicarbonate-rich mineral water has been shown to improve urinary inhibitors for crystallization, mainly citrate and magnesium [49].…”
Section: Implications For Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Die pH-Anhebung beruht auf einer Erh ö hung der Alkalireserve durch Hydrogenkarbonatzufuhr. Die erreichten pH-Werte liegen auch in unserer Studie in dem f ü r Kalziumoxalatsteine geforderten Bereich zwischen 6,5 und 7[32] . Die Erh ö hung des pH-Wertes ist nicht nur bei Harns ä uresteinen von Relevanz.…”
unclassified